Trabalho pedagógico na alfabetização: uma travessia dialética em construção - De Toni, Dulcineia Libraga Papalia (2017)
The present dissertation on Pedagogical Work in Literacy is inserted in the Research Line 02 - School Practices and Public Policies and is based on Kairós - Group of Studies and Research on Work, Public Policies and Education, both linked to the Postgraduate Program in Education of the Federal University of Santa Maria. During my graduation in Pedagogy, instigated by the issues experienced in the school through the PIBID, I was motivated to study the pedagogical work in literacy. As there are many researches developed in the area of Education, after defining the theme addressed in this project, the state of knowledge was realized, which sought to find existing academic productions on pedagogical work and literacy. However, there were few studies on the subject, on pedagogical work we found studies linked to pedagogical practice, pedagogical coordination and pedagogical orientation. Regarding literacy, studies are related to the practices of literacy teachers, to literacy methods, among others. The few papers found resulted as justification, revealing the importance of a study on the chosen theme. In this direction, this research project had, as problematization, to analyze which meanings of the pedagogical work emerge from the discourse of the literacy teachers of the Santa Maria Municipal Network. Its main objective was to analyze the conception of literacy teachers about pedagogical work. In relation to the specific objectives, they sought to understand the meanings produced by literacy teachers about their work and to contrast the advances and setbacks of literacy. As a theoretical-methodological contribution, the work was based on dialectical historical materialism, which allowed making some crossings during the course of the research, highlighting the centrality of the category Work. Based on the crossings, it was concluded that there would be no way to study Pedagogical Work in Literacy, without first looking at the history of education and the capitalist interests about it. Another issue is the distancing between theory and reality found in schools, as well as the antagonism between the proposed educational policies and their implementation. Finally, the considerations point to the need to look at the training of teachers, preparing them for the work they will perform at school, in the case of pedagogical work, and, after that, give voice to them, because they are who experience every day the innumerable factors that affect the school. Therefore, considering the continuous movement of phenomena and the history of humanity, the considerations reaffirm the belief in the conclusion of this study, since they continue in constant movement to attend to the phenomena that present themselves in relation to the pedagogical work in literacy - a dialectical crossing under construction.